INSECTICIDAL, ANTIBACTERIAL, AND ANTIRADICAL ACTIVITY OF NICOTIANA PLUMBAGINIFOLIA VIV. (SOLANACEAE) - Tr, Prashith Kekuda; Hl, Raghavendra; Mr, Rajesh; Hc, Avinash (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objectives: Nicotiana plumbaginifolia Viv. belongs to the family Solanaceae. The present study was carried out to determine insecticidal, antibacterial, and antiradical activity of aerial parts of N. plumbaginifolia. Methods: Extraction was carried out by maceration process using methanol. Insecticidal activity was assessed, in terms of larvicidal effect, against II and IV instar larvae of Aedes aegypti. Antibacterial activity was evaluated against a panel of 7 bacteria by agar well diffusion assay. Antiradical activity was determined using 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2-azinobis 3-ethylbenzothiazoline 6-sulfonate (ABTS) free radical scavenging assays. Results: The extract was found to cause dose-dependent mortality of larvae of A. aegypti. The lethal concentration 50 value of extract for II and IV instar larvae was found to be 0.41 and 0.99 mg/ml, respectively. Extract was effective in inhibiting all bacteria. Gram-positive bacteria displayed marked susceptibility when compared to Gram-negative bacteria. Bacillus cereus and Escherichia coli were susceptible to highest and least extent, respectively. Extract scavenged both DPPH radicals and ABTS radicals dose dependently. Extract scavenged ABTS radicals more efficiently (inhibitory concentration [IC50] value 13.51 Î¼g/ml) when compared to DPPH radicals (IC50 value 17.43 Î¼g/ml). Conclusions: The plant N. plumbaginifolia appears to be a promising resource for developing agents with insecticidal, antibacterial, and antiradical activity. The observed bioactivities could be attributed to the presence of phytochemicals which are to be isolated, characterized, and subjected for bioactivity determinations. The plant can be used to prevent arboviral diseases, infectious diseases, and oxidative damage.